The geography of tourism and recreation : Environment, place and space - Hall, C. Michael; Page, Stephen J. (New York Routledge, 2006)
Contents: introduction: tourism matters; the demand for recreation and tourism; the supply of recreation and tourism; the impacts of tourism and recreation; urban recreation and tourism;...
Includes bibliographical references and index
Keywords: Quản trị kinh doanh